2023
DOI: 10.1111/clr.14102
|View full text |Cite
|
Sign up to set email alerts
|

Implant survival/success and peri‐implant outcomes of titanium‐zirconium mini implants for mandibular overdentures: Results from a 1‐year randomized clinical trial

Abstract: ObjectiveTo report the 1‐year implant survival/success and peri‐implant outcomes of mandibular overdentures retained by four titanium‐zirconium mini implants (Straumann® Mini Implant System), and to assess how surgery and loading protocols influence these outcomes.Materials and MethodsA 2 × 2 factorial randomized clinical trial (RCT) tested the combined effects of two loading protocols (immediate or delayed) and two surgical approaches (flapless or flapped) on the success/survival of the mini implants, and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Four Roxolid ® MDIs have been proposed for the retention of a mandibular OD, and six for the retention of a maxillary OD. Outcomes of four Roxolid ® alloy MDIs retaining a mandibular OD in a prospective clinical study are available only for one year of their clinical use but with excellent results [26]. Due to the very good mechanical properties of the new Ti-Zr mini-implant system and the excellent osseointegration of the alloy, it would be interesting to find out whether less than the recommended four Ti-Zr mini-implants inserted in the mandible as single-units can successfully support a mandibular OD.…”
Section: Introductionmentioning
confidence: 99%
“…Four Roxolid ® MDIs have been proposed for the retention of a mandibular OD, and six for the retention of a maxillary OD. Outcomes of four Roxolid ® alloy MDIs retaining a mandibular OD in a prospective clinical study are available only for one year of their clinical use but with excellent results [26]. Due to the very good mechanical properties of the new Ti-Zr mini-implant system and the excellent osseointegration of the alloy, it would be interesting to find out whether less than the recommended four Ti-Zr mini-implants inserted in the mandible as single-units can successfully support a mandibular OD.…”
Section: Introductionmentioning
confidence: 99%
“…Although the survival rates of MDIs were described to be comparable to those of standard implants [30,32], another systematic review indicated significant differences between the three categories of narrow diameter implants (NDIs) compared with standard diameter implants [14]: While NDIs of Categories 2 and 3 had comparable survival rates, NDIs of Category 1, with a diameter of <2.5 mm or less, showed a noticeably increased risk of implant loss, with an odds ratio of 4.54 (CI: 1.51-13.65). Although novel mini implant systems show promising short-term data [33], it should be noted that none of the above-mentioned systematic reviews included long-term data. The 100% implant survival rate after 10 years in the present study could be related to the O-rings that reduce the force on the implants.…”
Section: Discussionmentioning
confidence: 99%
“…The novel Roxolid ® tissue-level mini-implant system has been on the dental market since 2020; therefore, only a few publications on it are available in the dental literature [ 27 , 28 ]. The manufacturer recommends the insertion of four Roxolid ® MDIs for mandibular OD retention and support.…”
Section: Introductionmentioning
confidence: 99%
“…The manufacturer recommends the insertion of four Roxolid ® MDIs for mandibular OD retention and support. The one-year study reported that the success rate of four single-unit Ti-Zr MDIs loaded by a mandibular OD was 100% in 74 patients, presenting a predictable treatment option even when flapless surgery and immediate loading were adopted [ 28 ]. However, the lack of studies dealing with the new Ti-Zr MDIs and the short period since the new system appeared on the market indicate the need for research at the in vitro level to obtain new knowledge for clinical application, especially when the insertion of less than four MDIs is being considered as an option.…”
Section: Introductionmentioning
confidence: 99%